Information and Communication Technologies in the Era of the Fourth Industrial Revolution: Technological Trends and Challenges in Engineering Education (2020)
Information and Communication Technologies have an important role in the deployment of current technological trends. In the era of the Fourth Industrial Revolution, several challenges are faced in both industry and education. For this reason, it is fundamental to know the technological advances and the changes that are necessary for professional profiles, curriculum, and teaching. This paper provides a comprehensive review of technological trends in the era of industry 4.0, and the challenges met for engineering education.